Demonstrative Evidence and Expert Opinion - Mason Ladd (Washington University Law Quarterly, 1956)
Demonstrative evidence has become the fashion of today in the trial of cases. The subject has reached epidemic proportions, and modern trials include this magic method of persuasion as one of the best gadgets yet devised to obtain jury verdicts and to aid the court in understanding the full meaning of factual and scientific evidence. The emphasis upon demonstrative evidence is a part of the times even though it has been used in one form or another as long as there have been court trials.
Keywords: Evidence; Expert witnesses